The Effect of Cord Blood Bile Acid Levels on the Meconium Passage in Utero in Normal Pregnancies - Saynur Sarıcı Yılmaz; Deniz Hızlı; Yaprak Engin Üstün; Engin Yılmaz; Elif Gül Yapar Eyi; Leyla Mollamahmutoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the effect of bile acids on meconium passage in utero in normal pregnancies.